(untitled) (Medico Legal Update, 2019)
Introduction: Sexual child abuse becomes a serious concern due to its alarming rate. It is claimed to bring serious hindrance in psychosocial development of children in the future. In 2015, the Survey on Violence against Children was carried out by the Ministry of Social Affairs, the Ministry of Women Empowerment and Child Protection and several agencies, in which it found prolonged and detrimental trauma in victims. The present study reveals sexual child abuse, legal protection against it, and approach in solving the case Material and Method: It is a literature study that aims at examining references to theories relevant to the problem Findings: The result reasserts the prevalence of child sexual abuse and the psychological impact of mental trauma, fear, shame, anxiety, even suicidal attempt. Conclusion: The “soft” punishment for child sex offender is palpable evidence. Hence, an approach based on transcendental perspective based on the spiritual values contained in Islamic